Tissue Reaction and Biocompatibility of Implanted Mineral Trioxide Aggregate with Silver Nanoparticles in a Rat Model - Zand, Vahid; Lotfi, Mehrdad; Aghbali, Amirala; Mesgariabbasi, Mehran; Janani, Maryam; Mokhtari, Hadi; Tehranchi, Pardis; Pakdel, Seyyed Mahdi Vahid (Iranian Endodontic Journal, 2016)
Introduction: Biocompatibility and antimicrobial activity of endodontic materials are of utmost importance. Considering the extensive applications of mineral trioxide aggregate (MTA) in dentistry and antimicrobial properties of silver nanoparticles, this study aimed to evaluate the subcutaneous inflammatory reaction of rat connective tissues to white MTA with and without nanosilver (NS) particles. Methods and Materials: Polyethylene tubes (1.1×8 mm) containing experimental materials (MTA and MTA+NS and empty control tubes) were implanted in subcutaneous tissues of seventy-five male rats. Animals were divided into five groups (n=15) according to the time of evaluation: group 1; after 7 days, group 2; after 15 days, group 3; after 30 days, group 4; after 60 days and group 5; after 90 days. The inflammatory reaction was graded and data was analyzed using the Kruskal-Wallis and Mann-Whitney U tests. Statistical significance was defined at 0.05. Results: Comparison of cumulative inflammatory reaction at all intervals revealed that the mean grade of inflammatory reaction to MTA, MTA+NS and control samples were 3, 2 and 2, respectively. According to the Mann-Whitney analysis there were no significant differences between MTA+NS and MTA (P=0.42). Conclusion: Incorporation of 1% nanosilver to MTA does not affect the inflammatory reaction of subcutaneous tissue in rat models. Keywords: Biocompatibility; Mineral Trioxide Aggregate; Nanosilver; Silver Nanoparticle